Branding the Middle East Communication Strategies and Image Building from Qom to Casablanca - Wippel, Steffen (Studies on Modern Orient, 2023)
This edited volume fills a gap in the research on place, product and personal branding in the Middle East and North Africa. It critically analyses processes of strategic communication and image building under conditions of globalisation, neoliberalisation and authoritarian rule. It looks at historical and contemporary branding efforts of different actors involved, their interests and motives and at the positioning of brands in time and space.